DESCRIPTIVE OF FAMILY PLANNING AND SPIRITUAL SERVICES AT THE VOLUNTARY COUNSELING AND TESTING CLINIC - Susanti; Widyoningsih Widyoningsih; Opi Irawansah (Jurnal Smart Kebidanan, 2024)
One way to anticipate HIV/AIDS transmission is through biopsychosociospiritual services, meaning seeing patients not only from physical, psychosocial but also spiritual/religious aspects. One intervention that can be carried out is by providing counseling to respondents about contraceptives and spiritual services to improve the quality of life of women with HIV/AIDS. Research Objectives: To determine family planning services and spiritual services at the VCT Clinic at the Cilacap Regional General Hospital. This research is a qualitative study describing the dimensions of family planning services and spiritual services at the VCT Clinic at the Cilacap Regional General Hospital with a sample of 3 women aged HIV/AIDS sufferers, Peer Support Group 2 people and VCT Clinic management 1 person. The sampling technique used purposive sampling and three participants were obtained. Research results: Family planning services have been integrated into VCT services, and there are no spiritual services by religious officers at the VCT Clinic. Suggestions need to improve family planning and spiritual services in VCT services.Keywords : Family Planning Services, Spiritualy Services, Women, HIV/AIDS